Airway infection, systemic inflammation and lung clearance index in children and adults with cystic fibrosis. Issue 2 (1st February 2018) - O'Neill, Katherine; Bradley, Judy M.; Reid, Alastair; Downey, Damian G.; Rendall, Jacqueline; McCaughan, John; Moore, John E.; Tunney, Michael M.; Elborn, J. Stuart
The lung clearance index (LCI) is a measure of ventilation distribution derived from multiple breath washout (MBW). It is a promising measure for monitoring early lung disease in cystic fibrosis (CF) [1–4] and is increasingly being used as a surrogate efficacy endpoint in CF clinical trials [5, 6]. LCI is reliable and more sensitive than forced expiratory volume in 1 s (FEV1 ) in detecting lung disease in infants, children and adults with CF [7–9], tracks early disease progression and symptoms [3], and predicts the onset of pulmonary exacerbations [10]. LCI has been shown to be elevated in infants and younger children with respiratory infection and correlates with airway inflammation, measured using a range of biomarkers in bronchoalveolar lavage [11–13]. However, there are few data on how LCI relates to markers of infection and inflammation in children >6 years and adults. LCI is a sensitive marker of infection and inflammation in clinically stable children and adults with cystic fibrosis http://ow.ly/vumZ30hzHL0